Improvement of Work Paper Learning Outcomes through Contextual Approaches and Problem-Posing Methods in SMA Negeri 3 Tarakan - Robertus Romy Siga (International Journal of Multi Discipline Science, 2020)
This research aimed to find out the increasing of learning outcomes in the accounting worksheet, the teacher’s activities of instructional management, and the student’s activities in the learning process at XI-IPS1 classes of SMA Negeri 3 Tarakan in the academic year 2019/2020. The type of this research was classified as Classroom Action Research (CAR) by applying the contextual approach and the problem-posing method. Data collection techniques were carried out by observation of the activities of students and teachers in the class, as well as learning achievement tests in each cycle. The data analysis technique used was a descriptive qualitative analysis conducted on teacher activities in the learning process, student activities in learning, and analysis of student learning outcomes. The result of this analysis showed that both teacher’s and student’s activities indicated gradual increases in the three cycles. Student’s learning outcomes also went up in each cycle. The observation of teacher’s activities in the first cycle was 4.04 and become 4.21 in the second cycle, and went up to 4.29 in the third cycle. The observation of student’s activities in the first cycle was 2.95 and become 3.45 in the second cycle and went up to 3.60 in the third cycle. Classically, passing rates in the first cycle were 41.66% and in the second cycle, it increased by 69.44% and went up to 88.89% in the third cycle. The strength in learning by the contextual approach and the problem-posing method were it can improve teacher’s activities, student’s activities, and learning outcomes. While the weaknesses were it needs more time to prepare the subject and the student with inadequacy in the problem-posing unable to follow the lessons. Based on the result of this research it could be concluded, the contextual approach and the problem-posing method are eligible in improving the student learning outcomes in the accounting worksheet.